"True" biocomposites with biopolyesters and date seed powder: Mechanical, thermal, and degradation properties. Issue 19 (23rd April 2014) - Mittal, Vikas; Chaudhry, A. U.; Matsko, Nadejda B.
ABSTRACT Biopolymers have gained research focus due to enhanced property profiles as well as need to replace the fossil fuel based polymeric materials. The generation of biocomposites with functional biofillers can lead to further enhancement of their potential. In this study, composites of date seed powder with biopolyesters poly(butylene adipate‐co‐terephthalate) (PBAT) and poly‐l‐lactide (PLA) have been demonstrated. The composites exhibited individual degradation peaks for the components in the thermogravimetric analysis (TGA), but still had suitable thermal performance confirmed by the dynamic TGA. The filler also modified the crystalline morphology of the polymers differently. The tensile modulus of the PBAT‐based composites had enhancement of more than 300% in the composite with 40% filler content. The PLA composites also enhanced the modulus marginally till 20% filler content, however, it was still significant due to the very high modulus of PLA as compared to PBAT. The rheological properties indicated the polymer still had viscous behavior even when high amount of filler was added. The storage and loss modulus of the composites enhanced with filler fraction, the PLA composites with 30 and 40% content, however, exhibited very high values probably due to filler aggregates and low filler‐polymer interfacial interactions. The filler particles were observed to be uniformly distributed in the polymer matrices, though some filler aggregates were also observed in the composites with higher filler fractions. After embedding in compost soil, the composites had significantly enhanced extent of biodegradation as compared to pure polymers, thus, confirming the "true" biocomposite nature. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40816.